Efficacy of phosphate carriers as foliar fertilizer on rainfed upland cotton (Gossypium hirsutum) - Venugopal, M V; Tarhalkar, P P; Singh, Jagvir (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the rainy season (kharifJ of 1991 and 1992 to study the effectiveness of foliar fertilization using different phosphate carriers. viz single superphosphate, diammonium phosphate, and the granular, liquid, zincated as well as potash-enriched ammonium polyphosphate, on ’JKHY 1’ hybrid upland cotton (Gossypium hirsutum L.) under rainfed condition. The foliar absorption continued till 72-96 hr after spraying, The P absorption with single superphosphate wasÂ only half of that with diammonium phosphate of polyphosphate (except zincated ammonium polyphosphate). Out of the P applied as liquid ammonium polyphosphate or diammonium phosphate. 75-80% was absorbed within 96 hr after the first spray, but the absorption pattern was different; the initial rate beingÂ faster with diammonium phosphate. Application of 6% of the nitrogen and 25% of the total recommended dose of phosphorus through foliar spray of ammonium polyphosphate increased the seed-cotton yield hy 14-18%. nitrogen uptake by 12-14%, phosphate uptake by 24-28% and apparent recovery or N and P by 17-18%, but did not improve the nutrient-utilization efficiency.